Mangrove-shrimp farming: A triple-win approach for communities in the Mekong River Delta. (15th April 2022) - Nguyen, Hai; Chu, Long; Harper, Richard J.; Dell, Bernard; Hoang, Hanh
Abstract: Balancing economic, environmental and social objectives usually challenges policymakers, but it is feasible. Using a unique household survey dataset with 98 households in Ca Mau Province, Vietnam, we found that integrating mangroves with shrimp farming, in a mangrove-aquaculture system (MAS), can support multiple objectives. The MAS provides the highest average benefit-cost ratio (BCR), from 2.7 to 2.9, while the BCR of surveyed intensive shrimp farms ranged from 1.1 to 1.2, and that of the traditional extensive shrimp farming systems was from 1.7 to 1.8. MAS was also the least expensive in terms of investment and suitable for people with limited financial capacity. MAS can also produce other economic and environmental benefits, such as from carbon mitigation, with less overall risk than the other systems. Our survey data show that mangrove coverage may contribute to economic efficiency; and the optimal mangrove coverage from the perspective of individual farmers (30%) was lower than what is demonstrated by empirical data (60%). While our findings draw from survey data in a specific location, they highlight the benefits of MAS as a possible triple-win approach towards sustainable development and also emphasise the importance of complementary programs, such as awareness enhancement, communication, and training.